3(a-1)=4(s+12)

Simple and best practice solution for 3(a-1)=4(s+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(a-1)=4(s+12) equation:


Simplifying
3(a + -1) = 4(s + 12)

Reorder the terms:
3(-1 + a) = 4(s + 12)
(-1 * 3 + a * 3) = 4(s + 12)
(-3 + 3a) = 4(s + 12)

Reorder the terms:
-3 + 3a = 4(12 + s)
-3 + 3a = (12 * 4 + s * 4)
-3 + 3a = (48 + 4s)

Solving
-3 + 3a = 48 + 4s

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 3a = 48 + 3 + 4s

Combine like terms: -3 + 3 = 0
0 + 3a = 48 + 3 + 4s
3a = 48 + 3 + 4s

Combine like terms: 48 + 3 = 51
3a = 51 + 4s

Divide each side by '3'.
a = 17 + 1.333333333s

Simplifying
a = 17 + 1.333333333s

See similar equations:

| (X-12)(5x-13)=0 | | N^2+8=6n | | 3y^2-17y-56=0 | | 2(-x)+x=13 | | 2(4x-5)=15 | | C^2-8=-13c+6 | | 0.5m+24=0.33m+4 | | 4(2-5x)= | | 0.5m+24=0.33+4 | | 3(2y-3)=15 | | 10x-3=3x+46 | | 0.2b-4=0.2b+5 | | x=36+8 | | 55-4x=5x+18 | | 3(k+3)=-15 | | 2x+7+5x+4= | | 67-5x=22x+19 | | y+8-2y=-28 | | 11-8x=48-15x | | 6-8x=32-15x | | 2x+8=4(x-16) | | 3x^2+19x+30=0 | | M-3=4k | | 6x+4=4x+14 | | 6-3(x+7)=15 | | n^2+8-6n=0 | | 4x-13=-113-10x | | 10x+13=3x+223 | | 11x+22=99 | | x^2-16x+63=y | | 10x-8x=48-22x | | -142-8x=10x+20 |

Equations solver categories